1991
DOI: 10.1164/ajrccm/143.3.528
|View full text |Cite
|
Sign up to set email alerts
|

Is the Clinical History a Satisfactory Means of Diagnosing Occupational Asthma?

Abstract: In some countries a diagnosis of occupational asthma for medicolegal purposes is made when a questionnaire is suggestive and the individual is exposed to a product known to be a sensitizer. The value of an open questionnaire administered by physicians with experience in occupational asthma is unknown, however. We prospectively assessed all subjects (162) referred to our clinic because their physicians thought their asthma might be work related. The medical questionnaire included questions about the nature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
7

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(95 citation statements)
references
References 14 publications
0
87
0
7
Order By: Relevance
“…However, these tests are not able to differentiate work-aggravated asthma from true OA, so that subjects who demonstrate work-related changes in airway obstruction, NSBH, or airway inflammation are currently diagnosed as having OA. In addition, several studies have shown that a substantial proportion of subjects who experience exacerbation of asthma symptoms at work, fail to demonstrate objective evidence of asthma worsening when they are exposed in their workplace or to the suspected agent in the laboratory [47,65,66]. Actually, the term "work-aggravated asthma" refers to self-reported symptoms but not to aggravation of any one of the physiological or pathological features of asthma.…”
Section: Work-aggravated Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…However, these tests are not able to differentiate work-aggravated asthma from true OA, so that subjects who demonstrate work-related changes in airway obstruction, NSBH, or airway inflammation are currently diagnosed as having OA. In addition, several studies have shown that a substantial proportion of subjects who experience exacerbation of asthma symptoms at work, fail to demonstrate objective evidence of asthma worsening when they are exposed in their workplace or to the suspected agent in the laboratory [47,65,66]. Actually, the term "work-aggravated asthma" refers to self-reported symptoms but not to aggravation of any one of the physiological or pathological features of asthma.…”
Section: Work-aggravated Asthmamentioning
confidence: 99%
“…Several limitations of these definitions should, however, be considered. The association between documented (new-onset) asthma, workrelated symptoms, and workplace exposure to agents known to cause asthma (criteria AzBzC3 in table 2 or AzBzCzD1 in table 3) provides only a low predictive value for the presence of OA [65], and may lead to gross overestimation of the true prevalence of the condition. On the other hand, the criterion new-onset asthma (criterion B in table 3) may result A. Healthcare professional9s diagnosis of asthma B.…”
Section: Purposes and Practical Applications Of The Definitionmentioning
confidence: 99%
“…In general, the patient's history alone is not sufficient for the diagnosis of occupational asthma and is more likely to exclude than to confirm the diagnosis of occupational asthma (38,42). Objective confirmation of the diagnosis is necessary for both appropriate medical care and compensation purposes.…”
Section: Diagnosismentioning
confidence: 99%
“…High antibody levels accompanying a characteristic history are often taken to be sufficient evidence for a diagnosis of occupational asthma. 14 In this study, we demonstrated 16 patients with CRM-induced occupational asthma who had complained of asthmatic symptoms with enough latent period and clear association between symptomatic aggravation and exposure to CRM. They showed either reversible airway obstruction or airway hyperresponsiveness to methacholine.…”
Section: Discussionmentioning
confidence: 68%